Mais rápido, mais alto, mais forte a superexploração e a saúde dos “atletas olímpicos” dos canaviais alagoanos - Yabe, Marcio (2013)
Faster, Higher, Stronger, translation of the Latin ―Citius, Altius, Fortius‖, motto of the modern Olympic Games, is used in this dissertation to make an analogy to the superexploitation of the sugar cane cutters of Alagoas (Brazil), as they increasingly need to perform faster, accumulate higher quantities of sugar cane and strike more strongly with their machetes, to guarantee the surplus value for the sugar factory owners of Alagoas.Our intention is to demonstrate how this professional category underwent an excessive exploitation, that could only result in damage to health and indelible marks in its corporeity, since the category was exposed throughout life to long working days, to the intensification of their work, and to the expropriation of the work necessary for their personal and familiar reproduction.This damage is proven through research carried out with workers between the ages of 41 and 67 years, who experienced working conditions before and after the deregulation of the sugar cane market in Brazil.Our theoretical basis rests on the Marxist theory of the exploitation of work, from which social scientists Ruy Mauro Marini and Raul Rojas Soriano derived the premises of super-exploitationandof Marxist medical sociology respectively.